Effects of the prone position on gas exchange and ventilatory mechanics and their correlations with mechanical power in burn patients with ARDS - Claudio Luciano Franck; Ehab G. Daoud (Journal of Mechanical Ventilation, 2024)
Background Prone position has many documented benefits on severe ARDS patients especially on mortality. The benefits in ARDS secondary to severe burns have not been fully documented. Aim To quantify the effects of prone positioning on gas exchange, ventilatory mechanics and their correlations with mechanical power in burn subjects with ARDS. Methods Cross-sectional observational analytical study that took place between January 2023 and October 2023 in Burns ICU in Brazil on subjects with moderate to severe ARDS ventilated with the volume controlled mode. Data were collected in the first prone positioning lasting 24 hours in the first 30 minutes after changing position and 30 minutes before returning to the supine position. The parameters of the components of mechanical ventilation and mechanical power calculated by the Gatinoni’s formula (respiratory rate, tidal volume, driving pressure, PEEP, peak and plateau pressures) were collected to evaluate ventilatory mechanics, and the values of the FiO2, PaO2, PaO2/FiO2 ratio, SpO2, EtCO2, PaCO2, PaCO2 - EtCO2 gradient to assess gas exchange. Mean, minimum and maximum values, 1st and 3rd quartiles, median and standard deviation are calculated. To compare the results obtained at the two evaluation moments, the student’s t-test for dependent samples and non-parametric Wilcoxon tests were considered. To evaluate the association between the variation between the two moments of each variable, and the variation in mechanical power, the Pearson correlation coefficient was calculated. The normality of the variables was assessed using the Jarque-Béra test. P values <0.05 indicated statistical significance. Results Except for EtCO2 (P 0.939) and PaCO2 (P 0.391) all other variables presented statistical significance in relation to their variations with reduction in FiO2 (P <0.001), reduction in PaCO2 - EtCO2 gradient (P 0.011), and increases in PaO2 (P 0.008), PaO2/FiO2 (P <0.001), SpO2 (P 0.004). In the analysis of variables, reduction in respiratory rate (P 0.142), VT (P 0.385), peak pressure (P 0.085), plateau pressure (P 0.009), PEEP (P 0.032), driving pressure (P 0.083), elastance (P 0.180), mechanical power (P < 0.001) with increase static compliance (P 0.414) and resistance pressure (P 0.443). Among the ventilatory mechanics variables, only the reductions in plateau pressure, PEEP, and mechanical power showed statistical significance. Conclusion The prone position in burns induced ARDS improved oxygenation and reduced arterial partial pressure to end tidal CO2 gradient, furthermore, reducing plateau pressures and PEEP, which in turn reduced mechanical power.